Administrative Management Training for Lembang Sarambu North Toraja Village Apparatus - Petrus, Petrus; Tinri, M. Darwis Nur; G, Muhammad Tahir (Jurnal Perjuangan dan Pengabdian Masyarakat : JPPM, 2025)
Administrative management training for village officials in Lembang SarambuVillage, North Toraja aims to improve the capacity and competence of village officials in managing village government administration professionally, orderly, and accountably. This activity provides a platform for village officials to understand good village government administration systems, master archive and document management techniques, learn village financial reporting mechanisms, understand regulations related to village management, and develop information technology skills for village administration. Through this training, it is hoped that village officials can improve the quality of public services, improve village governance systems, increase transparency and accountability in village fund management, and create good governance at the village level which has an impact on improving community welfare.